Organization and Productivity in Backward Economies - Kilby, Peter (Quarterly Journal of Economics, 1962)
Journal Article Organization and Productivity in Backward Economies Get access Peter Kilby Peter Kilby Enugu, Eastern Nigeria Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 76, Issue 2, May 1962, Pages 303–310, https://doi.org/10.2307/1880822 Published: 01 May 1962